Makna Simbol Tradisi Notak Manjang Suku Dayak Kubin Desa Tiong Keranjik dalam Prinsip Metafisika Simol Karl Jaspers - FEBRI RABUNI, PAULUS; ARMADA RIYANTO , FX. EKO (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2024)
The notak manjang tradition is a tradition of welcoming guests from the Dayak Kubin tribe. This tradition is usually used at weddings. The Dayak Kubin tribe believes that notak manjang is a tradition passed down from generation to generation by their ancestors. Long notes have certain meaning and value. The meaning that the author wants to research is the meaning of the existence of the Dayak Kubin tribe through symbols. The author conducted an analysis in Tiong Keranjik Village, Belimbing Hulu District, Melawi Regency. The aim of this article is to look at the meaning of symbols in the notak manjang tradition from the perspective of Karl Jaspers, an existentialist philosopher from Germany. The method used is the literature review method. Apart from that, the author also uses an ethnographic approach. The ethnographic approach is a research method that pays attention to the daily lives of local people in cultural aspects. Then, the author also used the interview method. The author creates a general interview framework, but not a standard set of questions. The focus of this article is to find the meaning of the notak manjang tradition through the symbols in it.